The readiness of MSMEs in facing ASEAN economic community 2015 - Tambunan, Tulus, 1956- (Economic issues, problems and perspectives series., 2014)
From a worldwide perspective, it has been recognized that micro, small and medium enterprises (MSMEs) play a vital role in economic development, as they have been the primary sources of job/employment creation and output growth. Even now it is generally believed that sustainable and inclusive economic development in developing regions (i.e. Asia, Africa and Latin America) depends to a large extent on the vibrant private sector, in particular MSMEs. This book is about MSMEs in ASEAN (Association of Southeast Asian Nations), providing most recent evidence on development and performance of the en.